TSC 신뢰성시험 규격 비교 및 신뢰도 예측 - 오봉식; 박상철; 장중순 (신뢰성 응용연구, 2019)
Purpose: Maintenance data for Korean traffic signal controller(TSC) shows that the replacement life is shorter than 10 years required. To investigate the causes, Korean and international TSC reliability standards are compared and MTBF of TSC is evaluated. Methods: Reliability test items of Korean, US, European, and Japanese TSC standards are compared as well as their test conditions. In addition, failures rates of main control unit CPU boards of 2 main control unit are evaluated based on MIL-HDBK-217F. Results: Domestic’s TSC requires 20 items compared to the European standard that defines 35 items. After installing and operating a new product of TSC, the actual way-out period was analyzed at 8.4 years until the replacement. This is a very short TSC endurance of 10 years. Thyristor LSU had no official tests with surge current applied. Corrective action is necessary to ensure that the confirmation procedure is carried out to improve such safety. Conclusions: Korean TSC standard requires less test items than EU, US and Japan. Some important tests like solar test, salt spray test, gas test and storage test are not specified. MTBFs of 2 CPU boards are evaluated to be less than 10 years.
Keywords: Traffic Signal Controller; Reliability Standards; Reliability Prediction; MTBF; MILHDBK-217F